Hack/slash (2007), omnibus volume 4 ebook - Seeley, Tim (Hack/Slash (2007), 2018)
A hefty brick of critically acclaimed horror goodness! Cassie & Vlad are launched into a new slasher hunt as they descend into a vast, dark conspiracy and must face old enemies, Victor Crowley (from the Hatchet series), Bomb Queen, Fantomah, and teenage pop music fans! Collects Hack/Slash Series 2 Issues #1-11, Annual - Murder Messiah, Annual Hatchet-Slash, Hack/Slash Holiday Special 2011, and Hack/Slash Meets Zombies Vs. Cheerleaders. . Author: Tim Seeley. Illustrator: Bryan Baugh, Kevin Mellon, Ryan Ottley . 2012 Hack/Slash, Inc..